2020
DOI: 10.1021/acs.orglett.0c02787
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed α-Alkylation of Ketones Using Secondary Alcohols to β-Disubstituted Ketones

Abstract: An assortment of aromatic ketones was successfully functionalized with a variety of unactivated secondary alcohols that serve as alkylating agents, providing β-disubstituted ketone products in good to excellent yields. Remarkably, challenging substrates such as simple acetophenone derivatives are effectively alkylated under this ruthenium catalysis. The substituted cyclohexanol compounds displayed product-induced diastereoselectivity. Mechanistic studies indicate the involvement of the hydrogen-borrowing pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…It also was later incorporated for further stereoselective studies, utilizing a chiral phosphine ligand to control the facial selectivity of hydride deposition to the enone intermediate, resulting in enantioenriched products as shown in Scheme ( 65 – 67 ). , The diastereoselective dialkylation of methyl ketones using diols to obtain cycloalkanes has also been performed with manganese , and iron catalysis . A recent study from Gunanathan and co-workers successfully demonstrated the alkylation of unsubstituted and unhindered acetophenone compounds with secondary alcohols by employing Ru-Macho as the catalyst and, contrary to previous reports, using a catalytic amount of base …”
Section: C–c Bond-forming Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…It also was later incorporated for further stereoselective studies, utilizing a chiral phosphine ligand to control the facial selectivity of hydride deposition to the enone intermediate, resulting in enantioenriched products as shown in Scheme ( 65 – 67 ). , The diastereoselective dialkylation of methyl ketones using diols to obtain cycloalkanes has also been performed with manganese , and iron catalysis . A recent study from Gunanathan and co-workers successfully demonstrated the alkylation of unsubstituted and unhindered acetophenone compounds with secondary alcohols by employing Ru-Macho as the catalyst and, contrary to previous reports, using a catalytic amount of base …”
Section: C–c Bond-forming Processesmentioning
confidence: 99%
“…140 A recent study from Gunanathan and co-workers successfully demonstrated the alkylation of unsubstituted and unhindered acetophenone compounds with secondary alcohols by employing Ru-Macho as the catalyst and, contrary to previous reports, using a catalytic amount of base. 141 The research discussed so far is predominantly limited to methyl ketone substrates using benzyl or long chain n-alkyl alcohols as alkylating agents. The ability to perform methylation to form α-branched products via the borrowing hydrogen method remained a challenge for many years due to the same reasons discussed earlier for N-methylation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 2020, a ruthenium pincer catalyzed α‐alkylation of ketones using unactivated secondary alcohols to β‐branched ketones was achieved by Gunanathan and co‐workers (Scheme 22). [28] Contrary to previously reported procedures, this strategy explored the utility of unsubstituted and nonhindered acetophenone compounds with a variety of secondary alcohols as alkylating agents. Remarkably, challenging substrates such as simple acetophenone derivatives were effectively alkylated under this ruthenium catalysis.…”
Section: The α‐Alkylation Of Ketonesmentioning
confidence: 99%
“…A comparison of the performances of reported protonresponsive catalysts was made (see, Scheme S2). It is apparent that 1 exhibits better catalytic efficacy in terms of lower base loading and higher TON and TOF values for both α-alkylation of ketones [38,110,121,[135][136][137][138] and β-alkylation of secondary alcohols. [87,94,104,106,139]…”
Section: β-Alkylation Of Secondary Alcohols Using Primary Alcoholsmentioning
confidence: 99%